Comparative Studies on Tributylammonium Chlorochromate Oxidation of Pentaammine Cobalt(III) Complexes of a-Hydroxy Acids Catalyzed by Benzalkonium Chloride - Dayanandhan, R.; Subramani, K. (Asian Journal of Chemistry, 2017)
A benzalkonium chloride (BKC) catalyzed oxidation of pentaammine cobalt(III) complexes of both bound and unbound a-hydroxy acids by tributylammonium chlorochromate (TriBACC) has been studied. Perchloric acid is adapted as a medium and the oxidative kinetics was contrived spectrophotometrically at room temperature. Rate of TriBACC oxidation is carried out at pseudo-first order conditions and rate constant was calculated. Absence of salt effect is observed on increasing NaClO4 concentration. Abatement in UV-visible absorbance at 503 nm for Co(III) complex confirms to nearly 100 % of initial absorbance. The complex [(NH3)5Co(III)-L]2+ shows inner sphere mechanism and induced electron transfer reaction yields 100 % Co(II). The product formed in this oxidation was analyzed and polymerization test was carried out. Comparative study of rate of TriBACC oxidation in presence of benzalkonium chloride is listed out.